2012
DOI: 10.1016/j.envres.2012.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Use of satellite-based aerosol optical depth and spatial clustering to predict ambient PM2.5 concentrations

Abstract: Satellite-based PM2.5 monitoring has the potential to complement ground PM2.5 monitoring networks, especially for regions with sparsely distributed monitors. Satellite remote sensing provides data on aerosol optical depth (AOD), which reflects particle abundance in the atmospheric column. Thus AOD has been used in statistical models to predict ground-level PM2.5 concentrations. However, previous studies have shown that AOD may not be a strong predictor of PM2.5 ground levels. Another shortcoming of remote sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(81 citation statements)
references
References 37 publications
(39 reference statements)
2
79
0
Order By: Relevance
“…This study also proved that high resolution GEOS AOD may be a better predictor of urban PM 2.5 than rough resolution MODIS AOD [35]. Lee et al [64] found that the R 2 value of MEM could reach 0.830 if missing AOD value were filled using a combination of cluster analysis and generalized additive models. In the mid-Atlantic region, Kloog et al [34] improved the MEM by adopting IPW for non-random missing AOD data, and obtained a value of 0.850 for the cross-validation of R 2 .…”
Section: Theory Background and Applicationmentioning
confidence: 80%
“…This study also proved that high resolution GEOS AOD may be a better predictor of urban PM 2.5 than rough resolution MODIS AOD [35]. Lee et al [64] found that the R 2 value of MEM could reach 0.830 if missing AOD value were filled using a combination of cluster analysis and generalized additive models. In the mid-Atlantic region, Kloog et al [34] improved the MEM by adopting IPW for non-random missing AOD data, and obtained a value of 0.850 for the cross-validation of R 2 .…”
Section: Theory Background and Applicationmentioning
confidence: 80%
“…It is interesting to see that within the urban areas of major cities in southern New England, the annual mean PM2.5 concentrations are obviously high as compared to their surrounding rural forest areas, but their spatial variations tend to be low. This might be because of the regional impacts of the transported PM2.5 pollution on these cities, as reported by a previous study [23]. …”
Section: Spatiotemporal Estimation Of the Pm25 Concentrationmentioning
confidence: 74%
“…There are extensive studies investigating the PM2.5-AOD relationship by the use of either an empirical statistical method (Engel-Cox et al, 2004;Liu et al, 2005Liu et al, , 2009Gupta et al, 2006;Koelemeijer et al, 2006;Gupta and Christopher, 2008;Paciorek et al, 2008;Di Nicolantonio et al, 2009;Schaap et al, 2009;Lee et al, 2012;Sorek-Hamer et al, 2013;Strawa et al, 2013;Chudnovsky et al, 2014;Ma et al, 2014) or a chemical transportation model (Liu et al, 2004;Van Donkelaar et al, 2006Kessner et al, 2013;Xu et al, 2015). In these studies, aerosol vertical distributions are estimated based on model simulation or under an assumption that aerosols are well mixed within the boundary layer and then decrease exponentially with height.…”
Section: Introductionmentioning
confidence: 99%